The sensory and motor representation of synchronized oscillations in the globus pallidus in patients with primary dystonia - Liu, X; Wang, S; Yianni, J; Nandi, D; Bain, P; Gregory, R; Stein, J; Aziz, T (2008)
In 15 patients with primary dystonia (six cervical and nine generalized dystonias) who were treated with bilateral chronic pallidal stimulation, we investigated the sensorimotor modulation of the oscillatory local field potentials (LFPs) recorded from the pallidal electrodes. We correlated these with the surface electromyograms in the affected muscles. The effects of involuntary, passive and voluntary movement and muscle-tendon vibration on frequency ranges of 0-3 Hz, theta (3-8 Hz), alpha (8-12 Hz), low (12-20 Hz) and high beta (20-30 Hz), and low (30-60 Hz) and high gamma (60-90 Hz) power were recorded and compared between cervical and generalized dystonia groups. Significant decreases in LFP synchronization at 8-20 Hz occurred during the sensory modulation produced by voluntary or passive movement or vibration. Voluntary movement also caused increased gamma band activity (30-90 Hz). Dystonic involuntary muscle spasms were specifically associated with increased theta, alpha and low beta (3-18 Hz). Furthermore, the increase in the frequency range of 3-20 Hz correlated with the strength of the muscle spasms and preceded them by ∼320 ms. Differences in modulation of pallidal oscillation between cervical and generalized dystonias were also revealed. This study yields new insights into the pathophysiological mechanisms of primary dystonias and their treatment using pallidal deep brain stimulation. © The Author (2008). Published by Oxford University Press on behalf of the Guarantors of Brain. All rights reserved.